Slump Test: Sensory Responses in Asymptomatic Subjects - Walsh, Jeremy (Journal of Manual & Manipulative Therapy, Inc., 2007)
The Slump Test is used as a fast, low-cost diagnostic tool in the evaluation of leg and back pain disorders. The purpose of this study was to identify the normative sensory responses to the Slump Test in asymptomatic subjects. Eighty-four subjects were tested using a standardized procedure by the same examiner to ensure consistency. Prevalence, intensity, location, and nature of responses at each stage of the Slump Test [Slumped Sitting (SS), Knee Extension (KE), Ankle Dorsiflexion (AD), and Cervical Extension (CE)] were recorded. Of the subjects, 97.6% reported a sensory response during the Slump Test. Prevalence of responses increased significantly from 29.8% at SS to 94% at KE and decreased significantly from 97.6% at AD to 65.5% at CE. Median intensity of responses increased significantly from 0/10 at SS, through 4/10 at KE, to 6/10 at AD, and then decreased significantly to 2/10 at CE. At SS, responses were located at the back or neck, but during the subsequent stages, responses were located most commonly in the posterior thigh, knee, and calf. In terms of nature, a number of different descriptors were used, the most common being “stretch,” “tight,” and “pull.” Approximately 80% of subjects reporting a response had complete or partial relief of this response following cervical extension, indicating that the normal response to the Slump Test may be considered a neurogenic response. This normative data may be used as a reference point when using the Slump Test in the examination of leg and back pain disorders.